PROTOCOL: Is the CEO/employee pay ratio related to firm performance in publicly traded companies? - Rousseau, Denise M.; Velghe, Cédric; Splenda, Ryan; Kim, Byeong Jo; Lee, Jangbum (Campbell systematic review, 2024)
One goal of this systematic review is to assess whether the pay ratio, that is, the relative difference between the compensation a firm's CEO receives and that of its nonmanagerial employees, is related to subsequent firm performance. A second goal is to identify factors influencing this relationship across publicly traded firms, including the pay ratio's perceived fairness by employees, the firm's business strategy, and related factors.